2019
DOI: 10.1186/s12882-019-1442-7
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory monitoring unmasks hypertension among kidney transplant patients: single center experience and review of the literature

Abstract: Background Disagreements between clinic and ambulatory blood pressure (BP) measurements are well-described in the general population. Though hypertension is frequent in renal transplant recipients, only a few studies address the clinic-ambulatory discordance in this population. We aimed to describe the difference between clinic and ambulatory BP in kidney transplant patients at our institution. Methods We compared the clinic and ambulatory BP of 76 adult recipients of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
7
0
1
Order By: Relevance
“…However, in the literature there are significant differences in the prevalence of white coat and masked hypertension, and dipping status. For example, the prevalence of white coat hypertension ranged from 3% to 24.1% (23,24,25), masked hypertension from 14% to 58% (23,24,25) and isolated nocturnal hypertension from 11% to 33% (23,25,26). Similarly, in regard to dipping status, normal dipping ranged from 5.4% to 26.7% of patients (22,26), reverse dipping in 20% of patients (26) and non-dipping BP from 53% to 94.6% of patients (22,24,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the literature there are significant differences in the prevalence of white coat and masked hypertension, and dipping status. For example, the prevalence of white coat hypertension ranged from 3% to 24.1% (23,24,25), masked hypertension from 14% to 58% (23,24,25) and isolated nocturnal hypertension from 11% to 33% (23,25,26). Similarly, in regard to dipping status, normal dipping ranged from 5.4% to 26.7% of patients (22,26), reverse dipping in 20% of patients (26) and non-dipping BP from 53% to 94.6% of patients (22,24,26).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prevalence of white coat hypertension ranged from 3% to 24.1% (23,24,25), masked hypertension from 14% to 58% (23,24,25) and isolated nocturnal hypertension from 11% to 33% (23,25,26). Similarly, in regard to dipping status, normal dipping ranged from 5.4% to 26.7% of patients (22,26), reverse dipping in 20% of patients (26) and non-dipping BP from 53% to 94.6% of patients (22,24,26). The difference in these studies is probably related to the method of office BP measurement (AOBP unobserved versus traditional measurement), the severity of CKD, and ethnic mix of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gluskin et al 34 compararam medidas de consultório e fora de consultório pela MAPA em adultos transplantados. A PA de consultório foi em média 128/79 mmHg.…”
Section: Medida Da Pa No Paciente Transplantado Renalunclassified
“…Hypertension is common in children after any solid organ transplants, and it has been demonstrated that hypertension rates are higher in 24-h ABPM assessments than in clinical BP measurements. 86,87 This is likely due to the prevalence of INH in transplant patients. The current clinical practice guidelines state that annual ABPM is appropriate for children with CKD.…”
Section: Can Normalization Of Inh Improve Hypertension-mediated Organ...mentioning
confidence: 99%